Basketball Elements in Physical Education Lessons for Primary School Students - Constantin CIORBĂ (ACROSS)
There are several ways to optimize the training process using various complexes of exercises, dynamic games and much more in physical education in school, including the primary level. At the same time, in recent years, sports games have become more and more popular, especially the game of basketball, which is quite attractive and dynamic, and quite popular among students.